(untitled) (Central Asian Journal of Medical Sciences, 2021)
Objective: Pancreatic necrosis is defined as acute necrotic collection and it occurs in 15-25% of patients with acute pancreatitis. Aim of this study is to investigate the use of marsupialization of omental bursa in combination with the semi-open packaging method to draining infected fluid collected from the omental bursa by suction pressure. Methods: We have performed a retrospective chart review of patients admitted to the General Surgery Department and Gastroenterology Department of The Third Central Hospital, and The First Central Hospital in Ulaanbaatar from November 1, 2008, to January 1, 2020, admitted with acute pancreatitis. After the complete debridement and lavage , upper and lower omental edges of the gastro-colic ligament were sewed to the peritoneum of upper and lower wound edges and negative pressure vacuum assisted closure was performed. Results: 155 patients aged 25-65 years participated in this study. The mean age was 38.98 ± 5.47, with 131 men (85%) and 24 women (15%). Post-opertaive complications occured in 118 (76.1%) cases of pancreatic necrosis after open surgery: the rate of complications was 45.8% in open packing, 21.3% in temporary closure, and 32.9% in vacuum closure. Wound healing time was 50.2 ± 3.6 in the open packing, while this time was shorted in both temporary closure and vacuum closure procedures (27.5 ± 3.05 and 28.1 ± 1.7, respectively). Conclusion: For pancreatic necrosis and inflammation, the use of marsupialization and semi-closed vacuum therapy reduces the number of recurrent surgeries with fewer complications. The postoperative wound closure of vacuum suction, was twice as short as open surgery (28.1 ± 1.7 days).